Presumed intimacy parasocial interaction in media, society and celebrity culture - Rojek, Chris (Cambridge, United Kingdom Polity Press, 2016)
"This engaging book examines how the ease with which modern social and media networks create a sense of intimacy which can be exploited by media, politicians and authoritarian intriguing thesis on how media creates relations where we are constant watchers of the lives of others.
Living with statistical men and women -- Chimerical risk management -- The shock waves of trauma -- The lost neighbour proposition and the collateral damage problem -- Horizontal frontierism: the juggernaut of character -- The accentuation of personality -- Vertical frontierism: four case studies -- Cracks in the mirror -- The gestural economy -- Institutional and counter-institutional gestural economies -- Nuda veritas.
Includes bibliographical references and index.
Keywords: Social interaction" -- Provided by publisher; Intimacy (Psychology) -- Social aspects; Celebrities; Mass media -- Social aspects